Role of nitric oxide synthase on brain GABA transaminase activity and GABA levels - Vega Rasgado Lourdes A.; Reyes Guillermo Ceballos; Vega Díaz Fernando (Acta Pharmaceutica)
In an attempt to clarify the controversial role of nitric oxide (NO) in seizures, the effects of NO on brain GABA transaminase (GABA-T) activity and GABA levels were investigated. To this aim, the effects of the substrate (l-arginine) and inhibitors (Nω-nitro-l-arginine methyl ester, 7-nitroindazole) of NO synthase (NOS) on GABA-T activity and GABA levels in vitro and ex vivo were analyzed. In vitro NO diminished GABA-T activity and increased GABA. Ex vivo NO modified GABA-T activity and GABA levels biphasically. Inhibition of endothelial and neuronal NOS (eNOS and nNOS) had opposite effects on GABA-T activity and GABA levels, even during seizures induced by pentylenetetrazole. Different effects of NO on GABA-T activity and on GABA levels, depending on the NOS isoform involved, may explain its contradictory role in seizures, the endothelial NOS acting as an anticonvulsant and the neuronal NOS as a proconvulsant. nNOS inhibitors may represent a new generation of antiepileptics.